2019
DOI: 10.25138/13.1.a3
|View full text |Cite
|
Sign up to set email alerts
|

A Humboldtian Critique of the University of the Philippines as the Flagship of Philippine Higher Education (Part II)

Abstract: For the Philippines to benefit from the ASEAN integration and globalization, in general, it must be able to mould highly educated citizens who can proactively engage themselves with the national, regional and international knowledge economies. 1 The Philippines has nine research universities that presumably lead its approximately 2,500 higher educational institutions in moulding these needed citizens. These nine research universities are the eight autonomous constituent units of the University of the Philippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…From the research results, it is shown that Humboldt is the one who came up with the idea of the "modern research university" [20]. The fundamental principles of Humboldt's university, such as science and truth is what must always be pursued on a regular and continuous basis; Universities should ensure freedom of teaching and freedom of learning (academic freedom); Universities need to realize the unity of research and teaching, science based on diversity and become a unity through philosophy.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…From the research results, it is shown that Humboldt is the one who came up with the idea of the "modern research university" [20]. The fundamental principles of Humboldt's university, such as science and truth is what must always be pursued on a regular and continuous basis; Universities should ensure freedom of teaching and freedom of learning (academic freedom); Universities need to realize the unity of research and teaching, science based on diversity and become a unity through philosophy.…”
Section: Discussion and Resultsmentioning
confidence: 99%